Determining the Validity and Reliability of ArtSci-S.P.D. Module On Year 5 Human Circulatory System - Ng, Kai Ling; Samsudin, Syakirah (Journal of learning theory and methodology (Online), 2024)
Objectives. The study aimed to determine the validity and reliability of the developed art-integration in science learning module, named ArtSci-S.P.D. Implementing the module has been carried out in order to ensure its suitability for using in further research. Materials and methods. The analysis approach for face validity was Fleiss’ kappa, while the content validity index (CVI) was employed to assess content validity, and the test-retest reliability method was used for measuring reliability. The calculation of test-retest reliability was performed by using Pearson’s correlation coefficient. Results. The findings show a positive tendency for evaluating the face and content validity (Fleiss’ kappa, k = 0.66; CVI > 0.78). Additionally, the module exhibits a high coefficient of reliability (r = 0.87). Conclusions. Thus, the module has been considered to be a valid and reliable tool for using in the actual study, thereby underscoring its efficacy.